Pengaruh Kompetensi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Kantor Kementerian Agama Kota Sorong - Muhammad Rayhan; La Ode Obi (Prodi Ekonomi Syariah IAIN Sorong, 2025)
This study aims to analyze the influence of competency and work environment on employee performance at the Ministry of Religious Affairs Office in Sorong City. This study employed a quantitative approach with an associative approach. The population comprised all 75 employees at the Ministry of Religious Affairs Office in Sorong City. The sampling technique used purposive sampling, with 65 respondents. Data collection was conducted through observation, questionnaires, and documentation. Data analysis was performed using SPSS version 27, using validity and reliability tests, multiple linear regression, t-tests, F-tests, and determination (R²) tests. The results indicate that competency variables partially have a positive and significant effect on employee performance, and that work environment variables also have a positive and significant effect on employee performance. Simultaneously, these two variables significantly contribute to improving employee performance at the Ministry of Religious Affairs Office in Sorong City. These findings emphasize the importance of improving competency and creating a conducive work environment in encouraging optimal employee performance.